PHYTOCHEMICAL AND ANTIFUNGAL ACTIVITY OF FOLK MEDICINAL PLANT BARLERIA PRIONITIS L. (VAJRADANTI) - PRAKASH, SWETA; DUBEY, KAMINI; KONTU, MEENUPRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the present study is to examine preliminary phytochemical investigations, qualitative analysis, and antifungal activity of Barleria prionitis L. leaf extracts. Methods: Aqueous and crude extract of B. prionitis leaf powder examined by Poisoned food assay to find out the inhibition (%) of fungi at 1 (%), 2 (%), and 3 (%) concentrations. Results: Flavones, flavanols, flavonols, saponins, and other phytochemicals were observed in leaf powder extract. B. prionitis crude extract inhibits A. flavus by 48.74 (%). Conclusion: This study shows useful preliminary, phytochemical investigation of B. prionitis L. leaf extracts as well as its antifungal activity. Further research needs to be carried out to purify other compounds contained and to conduct bioactivity assays. The leaves crude extract has depicted antifungal activity against Aspergillus flavus and Aspergillus niger. The aqueous extract of leaves seemed to not affect the fungal strains that were examined. The findings suggest that crude extracts of Barleria prionitis L. leaves provide the substantial potential for the development of a completely new broad range of antifungal herbal formulations.